A preparation method of screen-printed white glaze for photovoltaic backplane glass
Through the synergistic effect of modified acrylic resin and modified titanium dioxide, a white glaze for photovoltaic backplane glass with high weather resistance and strong impact resistance was prepared, which solved the problem of poor weather resistance of existing photovoltaic glass glaze and significantly extended the service life.
Patent Information
- Application Number
- CN202411569994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The titanium dioxide of existing photovoltaic glass glaze has lattice defects and photocatalytic active sites due to unmodified treatment, which leads to the release of oxygen atoms under ultraviolet light, shortening service life, and poor dispersion in the solvent, prone to whitening, aging, loss of light, and poor weather resistance.
Modified acrylic resin and modified titanium dioxide were used to prepare white glaze for photovoltaic back plate glass through screen printing technology. Modified titanium dioxide is ball milled and vibrating screened by ceramic ball mill, combining the synergistic effects of silicon envelope, phosphorus, fluorine and talc to improve the weather resistance and dispersion of titanium dioxide.
The silicon envelope of modified titanium dioxide prevents photocatalytic reactions, phosphorus and fluorine elements increase whiteness and reflectivity, and talc enhances hardness and wear resistance, significantly improves the weather resistance, impact resistance, hydrophobicity and corrosion resistance of screen-printed white glaze, and extends the service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic components and glass glazes, and in particular, relates to a method for preparing screen-printed white glaze for photovoltaic backplane glass. Background Art
[0002] Double-glass photovoltaic modules are composed of front glass, back glass and solar cells. The cells are connected in series and parallel by wires to the lead ends to form photovoltaic cell modules. They are particularly suitable for relatively harsh climate environments, such as photovoltaic power stations in areas with high humidity. In order to effectively improve the efficiency of double-glass modules, in addition to using white packaging materials such as EVA (ethylene-vinyl acetate copolymer) and POE (in-situ polymerization thermoplastic elastomer of ethylene and octene), photovoltaic glass glaze can also be applied to the back glass. Photovoltaic glass glaze is composed of glass powder, titanium dioxide, ink oil and other parts. It is coated on the surface of the back glass through screen printing technology to make it highly reflective. Its main advantage is that it can be directly used as a building material product without repeated construction. Its safety performance such as impact resistance is higher than that of ordinary photovoltaic modules, and its light transmission performance is improved. At the same time, it can play a dual role of decoration and sunshade.
[0003] However, the titanium dioxide used in photovoltaic glass glazes in the prior art has lattice defects and photocatalytic active sites on its surface because it has not been modified. Therefore, after being excited by ultraviolet light energy, the oxygen atoms on the titanium dioxide lattice will lose electrons and be released. These active oxygen species will oxidize and degrade the organic matrix in the surrounding environment, shortening the service life of titanium dioxide products. At the same time, titanium dioxide exhibits poor dispersibility in solvents and is prone to whitening, aging, and loss of gloss under the erosion of light, rain, wind, and air. Therefore, the weather resistance of screen-printed white glaze in the prior art is poor, and it is urgent to design and prepare a screen-printed white glaze for photovoltaic backplane glass with good weather resistance and strong impact resistance to expand the application range of photovoltaic backplane glass and meet market demand. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing screen-printed white glaze for photovoltaic backplane glass.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing screen-printed white glaze for photovoltaic backplane glass comprises the following steps:
[0007] (1) The monomer, styrene, coupling agent, molecular weight regulator and 90% initiator are mixed evenly, and slowly added to 60% solvent at a temperature of 140-150°C within 6-8 hours. After the addition is completed, the temperature is kept for reaction for 1-2 hours, and then 10% initiator is added. After the reaction is continued for 1-2 hours, the temperature is lowered to 70-80°C, and 40% solvent is added. The mixture is stirred thoroughly until the mixture is evenly mixed, and then the pH value of the system is adjusted to 8-9 with a pH regulator to obtain a modified acrylic resin;
[0008] (2) Fully stirring the solvent, modified acrylic resin, and fumed silica to obtain varnish;
[0009] (3) ball-milling the modified titanium dioxide in a ceramic ball mill, vibrating and screening, and finally mixing with deionized water for slurrying to obtain a titanium dioxide slurry containing 20 wt% of the modified titanium dioxide;
[0010] (4) Stir the varnish and dispersant evenly, add glass powder and titanium dioxide slurry, and stir until there is no agglomeration. Then add leveling agent and defoaming agent in turn, stir and grind to obtain screen printing white glaze.
[0011] Furthermore, the modified acrylic resin in step (1) comprises the following raw materials in parts by weight: 70-80 parts of monomer, 10-20 parts of styrene, 5-10 parts of coupling agent, 1-2 parts of molecular weight regulator, 3-7 parts of initiator, 2-4 parts of pH regulator, and 65-80 parts of solvent.
[0012] Furthermore, the monomer in step (1) is one or more of acrylic acid, glycidyl tert-butyl carbonate, hydroxyethyl acrylate, methyl methacrylate, isobornyl methacrylate, and butyl acrylate.
[0013] Furthermore, in step (1), the coupling agent is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.
[0014] Furthermore, in the step (1), the molecular weight regulator is 2,4-diphenyl-4-methyl-1-pentene.
[0015] Furthermore, in the step (1), the initiator is one or both of di-tert-butyl peroxide and di-tert-amyl peroxide.
[0016] Furthermore, in step (1), the pH regulator is 2-amino-2-methyl-1-propanol.
[0017] Furthermore, the varnish in step (2) comprises the following raw materials in parts by weight: 70-80 parts of solvent, 30-40 parts of modified acrylic resin, and 2-6 parts of fumed silica.
[0018] Furthermore, the solvent is one or more of diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, tripropylene glycol methyl ether, and tripropylene glycol butyl ether.
[0019] Furthermore, the modified titanium dioxide in step (3) is prepared by the following steps:
[0020] S1. At room temperature and under nitrogen protection, add 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, DBU (1,8-diazobisspiro[5.4.0]undec-7-ene) and DMF (N,N-dimethylformamide) into a dry three-necked flask, stir evenly and heat to 60°C, then slowly add bis[3-(triethoxysilyl)propyl]amine. After the addition is complete, keep the temperature to react for 48 hours. After the reaction is completed, distill under reduced pressure to obtain intermediate 1; the amount ratio of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, bis[3-(triethoxysilyl)propyl]amine, DBU and DMF is 25.9mL:46.4mL:3mL:200mL;
[0021] Under the catalytic action of DBU, the molar ratio of 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane to bis[3-(triethoxysilyl)propyl]amine is controlled to be 1:1.05-1.1, and 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane and bis[3-(triethoxysilyl)propyl]amine undergo Michael addition reaction;
[0022] S2, titanium dioxide and deionized water were stirred and heated to 80°C, and then polycarboxylate was added, and the pH was adjusted to 10 with 1 mol / L sodium hydroxide solution under stirring, and then 100 g / L water glass containing 28 wt% silicon dioxide was added, and the mixture was stirred for 1 hour and then cooled to room temperature, filtered, washed with deionized water, dried, and ground to obtain intermediate 2; the amount ratio of titanium dioxide, water glass, and polycarboxylate was 35 g:47.2 mL:0.08 g;
[0023] Silicon is directly connected to the surface hydroxyl Ti-OH group of titanium dioxide in the form of Si(OH)4, which changes the active Ti-OH group into a Ti-O-Si bond. Silicon is then precipitated on the surface of titanium dioxide particles in the form of Si(OH)4 to form a coating. The silicon coating makes it difficult for titanium dioxide to react with oxygen molecules and water molecules in the surrounding environment to generate active oxygen species, and it is not easy to yellow, powder, or whiten. Its weather resistance is more stable and durable.
[0024] S3. Disperse intermediate 2, aluminum dihydrogen tripolyphosphate and talcum powder in deionized water, add acetic acid to adjust the pH to 4, stir for 30 minutes, and transfer to a three-necked flask; disperse intermediate 1 in anhydrous ethanol, stir for 15 minutes, and transfer to the above three-necked flask. After the transfer is completed, heat to 65°C and react for 1 hour. After the reaction is completed, cool to room temperature, centrifuge, take the precipitate, ultrasonically vibrate in anhydrous ethanol for 10 minutes, and dry to obtain modified titanium dioxide; the dosage ratio of intermediate 2, intermediate 1, aluminum dihydrogen tripolyphosphate, talcum powder, deionized water and ethanol is 40g:3g:0.8g:8g:250mL:20mL.
[0025] The silane oxygen bonds in intermediate 1 are hydrolyzed and condensed to form Si-O-Si and Si-OH, which can form chemical bonds with intermediate 2, aluminum dihydrogen tripolyphosphate, and hydroxyl groups on the surface of talcum powder, so that the modified titanium dioxide can be evenly dispersed in the screen-printed white glaze and fully play its role.
[0026] The titanium dioxide in the modified titanium dioxide has a silicon coating on its surface, which makes it less likely for titanium dioxide to undergo photocatalytic reactions, and thus the modified titanium dioxide has more stable and excellent weather resistance. The modified titanium dioxide also contains fluorine atoms, which can enhance the hydrophobic properties of the modified titanium dioxide. The rich phosphorus element in the modified titanium dioxide can not only improve the whiteness of the white glaze and thus increase the reflectivity of light, but also minimize the anisotropy of the lattice expansion, reduce the generation of microcracks during the cooling process, improve the material's heat shock resistance, and synergistically improve the weather resistance of the glaze layer. The talc in the modified titanium dioxide has good suspension and fluidity, which can improve the flatness and glossiness of the screen-printed white glaze surface, while also increasing the hardness of the screen-printed white glaze, improving its wear resistance and corrosion resistance, and thus extending its service life. The modified titanium dioxide also contains carbon-carbon double bonds, which can react chemically with the unreacted carbon-carbon double bonds in the modified acrylic resin in the varnish under the action of the unreacted initiator. The modified titanium dioxide can then be further dispersed in the screen-printed white glaze to fully exert its effect, thereby improving the weather resistance, impact resistance, hydrophobicity, wear resistance and corrosion resistance of the screen-printed white glaze.
[0027] Furthermore, in step (4), the white glaze comprises the following raw materials in parts by weight: 18-24 parts of varnish, 0.5-1.5 parts of dispersant, 40-50 parts of glass powder, 30-40 parts of titanium dioxide slurry, 0.5-1 parts of leveling agent, and 0.5-1 parts of defoaming agent.
[0028] Furthermore, the dispersant in step (4) is one or more polycarboxylate sodium salt type dispersants.
[0029] Furthermore, the glass powder in step (4) is a low melting point glass powder, with a softening temperature of 400-500°C and a full melting temperature of 500-600°C.
[0030] Furthermore, the leveling agent in step (4) is one or more BYK type water-based leveling agents.
[0031] Furthermore, the defoaming agent in step (4) is one or more of organic silicon defoaming agents.
[0032] The beneficial effects of the present invention are as follows: the surface of titanium dioxide in the modified titanium dioxide has a silicon coating, so titanium dioxide is not prone to photocatalytic reaction, and has excellent and stable weather resistance. In addition, there is a chemical reaction between the modified titanium dioxide and the varnish, so the modified titanium dioxide has good dispersibility in the white glaze, can give full play to the anti-aging effect, and protect the screen-printed white glaze for a long time, greatly extending its service life; the phosphorus element, fluorine element and talc in the modified titanium dioxide work synergistically, further improving the impact resistance, weather resistance, hydrophobicity and corrosion resistance of the screen-printed white glaze. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1, preparing modified titanium dioxide, the specific steps are as follows:
[0035] S1. Add 25.9 mL of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 3 mL of DBU and 200 mL of DMF into a 500 mL dry three-necked flask at room temperature and under nitrogen protection. Stir evenly and heat to 60°C. Then slowly add 46.4 mL of bis[3-(triethoxysilyl)propyl]amine. After the addition is complete, keep the mixture warm for 48 hours. After the reaction is complete, distill under reduced pressure to obtain intermediate 1.
[0036] S2, 35g titanium dioxide and 210mL deionized water were stirred and heated to 80°C, and then 0.08g polycarboxylate was added, and the pH was adjusted to 10 with 1mol / L sodium hydroxide solution under stirring, and then 47.2mL of 100g / L water glass containing 28wt% silicon dioxide was added, and the mixture was stirred for 1h and then cooled to room temperature, filtered, washed with deionized water, dried, and ground to obtain intermediate 2;
[0037] S3, take 40g of intermediate 2, 0.8g of aluminum dihydrogen tripolyphosphate, and 8g of talcum powder, disperse them in 250mL of deionized water, add acetic acid to adjust the pH to 4, stir for 30min, and transfer them to a three-necked flask; disperse 3g of intermediate 1 in 20mL of anhydrous ethanol, stir for 15min, and transfer them to the above three-necked flask. After the transfer is completed, heat to 65℃ and react for 1h. After the reaction is completed, cool to room temperature, centrifuge, take the precipitate, ultrasonically oscillate it in anhydrous ethanol for 10min, and dry it to obtain modified titanium dioxide.
[0038] Example 2, preparing titanium dioxide, the specific steps are as follows:
[0039] The remaining steps remain unchanged, only the talcum powder and aluminum dihydrogen tripolyphosphate in step S3 of Example 1 are removed to prepare modified titanium dioxide.
[0040] Example 3, preparing titanium dioxide, the specific steps are as follows:
[0041] The remaining steps remain unchanged, only step S2 of Example 1 is removed, and the intermediate 2 in step S3 is replaced by titanium dioxide without any treatment to prepare modified titanium dioxide.
[0042] Example 4, preparing titanium dioxide, the specific steps are as follows:
[0043] The remaining steps remain unchanged, except that the intermediate 1 in step S3 of Example 1 is replaced by 3-aminopropyltrimethoxysilane to prepare modified titanium dioxide.
[0044] Example 5, preparing screen-printed white glaze, the specific steps are as follows:
[0045] (1) 30 parts of acrylic acid, 30 parts of hydroxyethyl acrylate, 10 parts of methyl methacrylate, 10 parts of styrene, 5 parts of vinyl trimethoxysilane, 1 part of 2,4-diphenyl-4-methyl-1-pentene and 2.7 parts of di-tert-butyl peroxide were mixed evenly, and slowly added to 26 parts of diethylene glycol butyl ether and 13 parts of dipropylene glycol methyl ether at a temperature of 140°C within 6 hours. After the addition was completed, the mixture was kept warm for reaction for 2 hours, and then 0.3 parts of di-tert-butyl peroxide was added. After the reaction was continued for 2 hours, the temperature was lowered to 70°C, and 17 parts of diethylene glycol butyl ether and 9 parts of dipropylene glycol methyl ether were added. The mixture was stirred thoroughly until the mixture was evenly mixed, and then 2 parts of 2-amino-2-methyl-1-propanol were used to adjust the pH value of the system to 8 to obtain a modified acrylic resin;
[0046] (2) 47 parts of diethylene glycol butyl ether, 23 parts of dipropylene glycol methyl ether, 30 parts of the modified acrylic resin obtained in step (1), and 2 parts of fumed silica were fully stirred to obtain varnish;
[0047] (3) The modified titanium dioxide obtained in Example 1 was ball-milled in a ceramic ball mill, vibrated and sieved, and finally mixed with deionized water for slurrying to obtain a titanium dioxide slurry containing 20 wt% of the modified titanium dioxide;
[0048] (4) 18 parts of the varnish prepared in step (2) and 0.5 parts of HYDROPALAT5040 dispersant are mixed evenly, 40 parts of low-melting-point glass powder and 30 parts of the titanium dioxide slurry prepared in step (3) are added, and the mixture is stirred until no lumps are formed. Then, 0.5 parts of BYK-333 leveling agent and 0.5 parts of BYK-024 defoaming agent are added in sequence, and the mixture is stirred and ground to obtain a screen-printed white glaze.
[0049] Example 6, preparing screen-printed white glaze, the specific steps are as follows:
[0050] (1) 30 parts of acrylic acid, 20 parts of tert-butyl glycidyl carbonate, 28 parts of isobornyl methacrylate, 16 parts of styrene, 8 parts of vinyl triethoxysilane, 1.6 parts of 2,4-diphenyl-4-methyl-1-pentene and 5.4 parts of di-tert-amyl peroxide were mixed evenly, and slowly added to 21 parts of dipropylene glycol butyl ether and 21 parts of tripropylene glycol methyl ether at a temperature of 145° C. within 7 hours. After the addition was completed, the mixture was kept warm for reaction for 1.5 hours, and then 0.6 parts of di-tert-amyl peroxide was added. The reaction was continued for 1.6 hours, and then the temperature was lowered to 75° C., and then 14 parts of dipropylene glycol butyl ether and 14 parts of tripropylene glycol methyl ether were added. The mixture was stirred thoroughly until the mixture was evenly mixed, and then 3 parts of 2-amino-2-methyl-1-propanol were used to adjust the pH value of the system to 8.5 to obtain a modified acrylic resin;
[0051] (2) 38 parts of dipropylene glycol butyl ether, 38 parts of tripropylene glycol methyl ether, 37 parts of the modified acrylic resin obtained in step (1), and 5 parts of fumed silica were fully stirred to obtain varnish;
[0052] (3) The modified titanium dioxide obtained in Example 1 was ball-milled in a ceramic ball mill, vibrated and sieved, and finally mixed with deionized water for slurrying to obtain a titanium dioxide slurry containing 20 wt% of the modified titanium dioxide;
[0053] (4) 21 parts of the varnish prepared in step (2) and 1 part of the XJ-5040 dispersant are mixed evenly, 45 parts of the low-melting-point glass powder and 38 parts of the titanium dioxide slurry prepared in step (3) are added, and the mixture is stirred until no lumps are formed. Then, 0.4 parts of BYK-302 leveling agent, 0.4 parts of BYK-320 leveling agent and 0.8 parts of BYK-024 defoaming agent are added in sequence, and the mixture is stirred and ground to obtain a screen-printed white glaze.
[0054] Example 7, preparing screen-printed white glaze, the specific steps are as follows:
[0055] (1) 30 parts of acrylic acid, 30 parts of methyl methacrylate, 20 parts of butyl acrylate, 20 parts of styrene, 10 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 2 parts of 2,4-diphenyl-4-methyl-1-pentene and 6.3 parts of di-tert-butyl peroxide were mixed evenly, and slowly added to 24 parts of diethylene glycol butyl ether, 12 parts of dipropylene glycol butyl ether and 12 parts of tripropylene glycol butyl ether at a temperature of 150°C within 8 hours. After the addition was completed, the mixture was kept warm for reaction for 1 hour, and then 0.7 parts of di-tert-butyl peroxide and di-tert-amyl peroxide were added. After the reaction was continued for 1 hour, the temperature was lowered to 80°C, and 16 parts of diethylene glycol butyl ether, 8 parts of dipropylene glycol butyl ether and 8 parts of tripropylene glycol butyl ether were added. The mixture was stirred thoroughly until the mixture was evenly mixed, and then 4 parts of 2-amino-2-methyl-1-propanol were used to adjust the pH value of the system to 9 to obtain a modified acrylic resin;
[0056] (2) 40 parts of diethylene glycol butyl ether, 20 parts of dipropylene glycol butyl ether, 20 parts of tripropylene glycol butyl ether, 40 parts of the modified acrylic resin obtained in step (1), and 6 parts of fumed silica were fully stirred to obtain varnish;
[0057] (3) The modified titanium dioxide obtained in Example 1 was ball-milled in a ceramic ball mill, vibrated and sieved, and finally mixed with deionized water for slurrying to obtain a titanium dioxide slurry containing 20 wt% of the modified titanium dioxide;
[0058] (4) 24 parts of the varnish prepared in step (2) and 1.5 parts of the SN-5040 dispersant are uniformly stirred, 50 parts of the low-melting-point glass powder and 40 parts of the titanium dioxide slurry prepared in step (3) are added, and the mixture is stirred until no lumps are formed. Then, 0.5 parts of BYK-333 leveling agent, 0.5 parts of BYK-354 leveling agent and 1 part of BYK-024 defoaming agent are added in sequence, and the mixture is stirred and ground to obtain a screen-printed white glaze.
[0059] Comparative Example 1, preparing screen-printed white glaze, the specific steps are as follows:
[0060] The remaining steps remain unchanged, only the modified titanium dioxide in Example 5 is replaced by titanium dioxide without any treatment, so as to prepare the screen-printed white glaze.
[0061] Comparative Example 2, preparing screen-printed white glaze, the specific steps are as follows:
[0062] The remaining steps remain unchanged, only the modified titanium dioxide in Example 6 is replaced by the modified titanium dioxide prepared in Example 2, thereby preparing the screen-printed white glaze.
[0063] Comparative Example 3, preparing screen-printed white glaze, the specific steps are as follows:
[0064] The remaining steps remain unchanged, only the modified titanium dioxide in Example 7 is replaced by the modified titanium dioxide prepared in Example 3, so as to prepare the screen-printed white glaze.
[0065] Comparative Example 4, preparing screen-printed white glaze, the specific steps are as follows:
[0066] The remaining steps remain unchanged, only the modified titanium dioxide in Example 7 is replaced by the modified titanium dioxide prepared in Example 4, so as to prepare the screen-printed white glaze.
[0067] Performance Testing
[0068] The white glazes of Examples 5-7 and Comparative Examples 1-4 were screen-printed onto the photovoltaic module glass using a 200-mesh screen and then cured to perform the following performance tests:
[0069] (1) Appearance: visual inspection;
[0070] (2) Reflectivity: tested using Konica Minolta's CM-26dG / 26d / 25d spectrophotometer;
[0071] (3) Adhesion: tested by the hundred-grid knife scratch method;
[0072] (4) Impact resistance: Tested in accordance with GB / T39814-2021 "Ultra-thin glass impact strength test method - falling ball impact method";
[0073] (5) High Pressure Cooking (PCT) Test: Refer to the standard T / CPIA0028.2-2021 "Glass for Photovoltaic Modules Part 2: Double-Glass Module Back Sheet Enhanced Reflection Coated Glass". Specifically, both the glass samples and the laminate samples are placed in a test box. The test temperature is 121±0.5°C, the relative humidity is 99-100%, and the test time is 48 hours. After the test, all samples are visually inspected to observe whether the glaze layer has delamination, blistering, cracking, powdering, or shedding. The photovoltaic reflectance R of the glass sample after aging is tested, and the photovoltaic reflectance attenuation value ΔR is calculated;
[0074] The test results of all items are shown in Table 1 below:
[0075] Table 1
[0076]
[0077] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0078] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing screen-printed white glaze for photovoltaic backplane glass, characterized in that: The following steps are involved: (1) Mix the monomer, styrene, coupling agent, molecular weight regulator and 90% by weight of initiator, add to 60% by weight of solvent at 140-150° C. within 6-8 hours, react for 1-2 hours, add 10% by weight of initiator, react for 1-2 hours, cool to 70-80° C., add 40% by weight of solvent, stir, and adjust the pH value of the system to 8-9 with a pH regulator to obtain a modified acrylic resin; (2) stirring the solvent, modified acrylic resin, and fumed silica to obtain varnish; (3) ball-milling, sieving and slurrying the modified titanium dioxide to obtain titanium dioxide slurry; (4) Stirring ink and dispersant, adding glass powder and titanium dioxide slurry, stirring, adding leveling agent and defoaming agent, stirring and grinding to obtain screen printing white glaze; Wherein, the modified titanium dioxide in step (3) is prepared by the following steps: S1. Add 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, DBU and DMF into a flask, stir and heat to 60°C, then add bis[3-(triethoxysilyl)propyl]amine, react for 48 hours, and distill under reduced pressure to obtain intermediate 1; the amount ratio of 1,6-di(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, bis[3-(triethoxysilyl)propyl]amine, DBU and DMF is 25.9mL:46.4mL:3mL:200mL; S2, stirring titanium dioxide and deionized water and heating to 80°C, adding polycarboxylate, adjusting the pH to 10 with sodium hydroxide solution, then adding water glass, stirring, cooling, filtering, washing, drying, and grinding to obtain intermediate 2; the amount ratio of titanium dioxide, water glass, and polycarboxylate is 35g:47.2mL:0.08g; S3. Take intermediate 2, aluminum dihydrogen tripolyphosphate and talcum powder in deionized water, add acetic acid to adjust the pH to 4, stir, and transfer to a flask; disperse intermediate 1 in anhydrous ethanol, transfer to the above flask after stirring, react at 65°C for 1h, cool, centrifuge, sonicate, and dry to obtain modified titanium dioxide; the dosage ratio of intermediate 2, intermediate 1, aluminum dihydrogen tripolyphosphate, talcum powder, deionized water and ethanol is 40g:3g:0.8g:8g:250mL:20mL.
2. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: The modified acrylic resin in step (1) comprises the following raw materials in parts by weight: 70-80 parts of monomer, 10-20 parts of styrene, 5-10 parts of coupling agent, 1-2 parts of molecular weight regulator, 3-7 parts of initiator, 2-4 parts of pH regulator, and 65-80 parts of solvent.
3. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: In step (1), the monomer is one or more of acrylic acid, tert-butyl glycidyl carbonate, hydroxyethyl acrylate, methyl methacrylate, isobornyl methacrylate, and butyl acrylate; the coupling agent is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, and 3-(methacryloyloxy)propyl trimethoxy silane.
4. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: In the step (1), the molecular weight regulator is 2,4-diphenyl-4-methyl-1-pentene; the initiator is one or both of di-tert-butyl peroxide and di-tert-amyl peroxide; and the pH regulator is 2-amino-2-methyl-1-propanol.
5. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: The varnish in step (2) comprises the following raw materials in parts by weight: 70-80 parts of solvent, 30-40 parts of modified acrylic resin, and 2-6 parts of fumed silica.
6. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: The solvent is one or more of diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, tripropylene glycol methyl ether and tripropylene glycol butyl ether.
7. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: The white glaze in step (4) comprises the following raw materials in parts by weight: 18-24 parts of varnish, 0.5-1.5 parts of dispersant, 40-50 parts of glass powder, 30-40 parts of titanium dioxide slurry, 0.5-1 parts of leveling agent, and 0.5-1 parts of defoaming agent.
8. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: In the step (4), the dispersant is one or more polycarboxylate sodium salt type dispersants; the glass powder is low melting point glass powder, the softening temperature is 400-500°C, and the full melting temperature is 500-600°C.
9. The method for preparing screen-printed white glaze for photovoltaic backplane glass according to claim 1, characterized in that: In the step (4), the leveling agent is one or more BYK type water-based leveling agents; and the defoaming agent is one or more silicone defoaming agents.
Citation Information
Patent Citations
Solvent-free nanometer modified epoxy weather-resistant type anticorrosive paint and preparation method thereof
CN102796439A
Novel modified titanium dioxide white antirust pigment and preparing method thereof
CN104194407A